Developing digitally enabled interventions for prison and probation settings: a review. Issue 2 (14th May 2018) - Morris, Jason; Bans, Manpreet Kaur
Abstract : Purpose: The purpose of this paper is to highlight some initial efforts within Her Majesty's Prison and Probation Service (HMPPS) to develop digitally enabled services supporting the rehabilitation of service users. It is not designed to set out either HMPPS policy on digital rehabilitative services or the position of HMPPS Interventions Services on this subject. Rather, it is a short exposition of the authors' views on the potential of digitally enabled strategies to enhance interventions in forensic settings. In this context, the authors will also describe the development of the first digitally enabled rehabilitation service accessed via HMPPS in-room computer terminals. Design/methodology/approach: The authors have reviewed current literature and outlined how the authors have and are aiming to add to this area of work. Findings: This general review outlines the authors' views on the potential of digitally enabled strategies for improving interventions in forensic settings. Originality/value: This paper is a short exposition of the authors' views on the potential of digitally enabled strategies to enhance interventions in forensic settings. In this context, the authors will also describe the development of the first digitally enabled rehabilitation service accessed via HMPPS in-room computer terminals.